Non-classical functions of nuclear pore proteins in ciliopathy - Chen, Yan; Zhang, Yuan; Zhou, Xiangyu (Frontiers in Molecular Biosciences, 2023)
Nucleoporins (NUPs) constitute integral nuclear pore protein (NPC) elements.Although traditional NUP functions have been extensively researched, evidence of additional vital non-NPC roles, referred to herein as non-classical NUP functions, is also emerging. Several NUPs localise at the ciliary base. Indeed, Nup188, Nup93 or Nup205 knockdown results in cilia loss, impacting cardiac left-right patterning in models and cell lines. Genetic variants of Nup205 and Nup188 have been identified in patients with congenital heart disease and situs inversus totalis or heterotaxy, a prevalent human ciliopathy. These findings link non-classical NUP functions to human diseases. This mini-review summarises pivotal NUP interactions with NIMA-related kinases or nephronophthisis proteins that regulate ciliary function and explores other NUPs potentially implicated in cilia-related disorders. Overall, elucidating the non-classical roles of NUPs will enhance comprehension of ciliopathy aetiology.